Anti-TNF Treatment for Extraintestinal Manifestations of Inflammatory Bowel Disease in the Swiss IBD Cohort Study. Issue 7 (27th April 2017) - Vavricka, Stephan R.; Gubler, Martin; Gantenbein, Claudine; Spoerri, Muriel; Froehlich, Florian; Seibold, Frank; Protic, Marijana; Michetti, Pierre; Straumann, Alex; Fournier, Nicolas; Juillerat, Pascal; Biedermann, Luc; et al.
Abstract : Background: Extraintestinal manifestations (EIMs) in patients with inflammatory bowel disease (IBD) are frequently observed. Little is known about the efficacy of anti–tumor necrosis factor (TNF) in EIM management. We assessed the effect of 3 anti-TNF agents (infliximab, adalimumab, and certolizumab pegol) on EIM evolution. Methods: Data on 1249 patients from the Swiss IBD Cohort Study (SIBDCS) were analyzed. All EIMs were diagnosed by relevant specialists. Response was classified into improvement, stable disease, and clinical worsening based on the physician's interpretation. Results: Of the 366 patients with at least 1 EIM, 213 (58.2%) were ever treated with an anti-TNF. A total of 299 treatments were started for 355 EIMs. Patients with EIM were significantly more often treated with anti-TNF compared with those without EIM (58.2% versus 21.0%, P < 0.001). Infliximab was the most frequently used drug (63.2%). In more than 71.8%, a clinical response of the underlying EIM to anti-TNF therapy was observed. In 92 patients (43.2%), anti-TNF treatments were started for the purpose of treating EIM rather than IBD. Response rates to anti-TNF were generally good and best for psoriasis, aphthous stomatitis, uveitis, and peripheral arthritis. In 11 patients, 14 EIM occurred under anti-TNF treatment. Conclusions: Anti-TNF was frequently used among patients with EIM. In more than 40%, anti-TNF treatments are started to treat EIM rather than IBD. Given the good response rates, anti-TNF seems to be a valuable option in the treatment of EIM, whereas appearance of EIM under anti-TNF does not seem to be a source of considerable concern.